(untitled) (Research, Society and Development, 2023)
Goiatuba is an inland city located in the southern region of the State of Goiás, it does not have large enterprises, however, it receives more than two thousand people daily in the university center that is installed there. The University Center of Goiatuba - UniCerrado, as it is called, stands out for providing quality knowledge, and offering graduation in 13 courses: Administration, Agronomy, Accounting, Law, Physical Education, Nursing, Civil Engineering, Physiotherapy, Environmental Management, Literature, Medicine, Dentistry and Pedagogy, which attract students from around 34 cities in the region, serving more than 2,725 students per semester. In the city, where the university center is located, there are no other institutions of the same size. Therefore, the purpose of this article is to verify if there is commuting, traffic on public roads and use of the institution’s facilities and if these are sufficient to guarantee the minimum comfort to students who travel to the institution and if there is any influence on the people who are installed in their vicinity. Secondary data were collected from a qualitative exploratory research, and primary data from the elaboration and application of a questionnaire, based on article 37 of the City Statute.